Comparing the Validity of Self-Report and Urinalysis for Substance Use among Former Inmates in the Northeastern United States: Substance Use Reporting Accuracy Among Inmates. (24th August 2018) - van den Berg, Jacob J.; Adeyemo, Samuel; Roberts, Mary B.; Bock, Beth C.; Stein, L.A.R.; Martin, Rosemarie A.; Parker, Donna R.; Clarke, Jennifer G.
ABSTRACT: Background: Problems with self-reported drug use include difficulties with recall and recognition as well as the desire to respond to questions in a socially desirable manner. Various methods have been developed to improve and/or validate estimates based on direct questioning of individuals regarding their substance use. For this study, we were interested in validating self-reported use of: 1) tobacco, 2) marijuana, and 3) other substances (i.e., heroin, cocaine, opiates, oxycodone, benzodiazepines, methamphetamine, phencyclidine, and barbiturates) employing urinalysis among inmates who participated in a randomized controlled trial of a smoking abstinence intervention in a tobacco-free prison located in the northeastern United States. Methods: Two-hundred and seven men and women with a mean age of 34.9 (standard deviation = 9.0) completed questions regarding their substance use on a 7-day Timeline Follow-Back and provided urine specimens three weeks following prison release. Results: Self-reported tobacco and marijuana use were highly consistent with urine drug testing in terms of overall agreement and Kappa (93.7% and.804 for tobacco, respectively; and 90.3% and.804 for marijuana, respectively); however, consistency was much lower for other drug use grouped together (62.7% and.270). Discussion : Although some former inmates may not accurately report substance use, our findings indicate that they are in the minority, suggesting that self-report is valid for tobacco and marijuana use but much less so for other drugs grouped together. Future research should be conducted with a larger and more diverse sample of former inmates to establish the generalizability of our findings from this study.